Improvement of reproductive performance comet fish (Carassius auratus auratus Linnaeus 1758) through the provision of meal cow’s brain as a natural GnRH - Ujang Subhan; Yuli Andriani; Kiki Haetami; Rosidah Rosidah; Abi Muhamad Abdillah (Jurnal Iktiologi Indonesia, 2017)
This study aimed to determine the effect of brain flour cow’s on feed in the performance of eggs and fecundity in fish comet. The research was conducted at the Faculty of Fisheries and Marine Sciences, University of Padjadjaran at November 2014 until January 2015. Freeze-drying of bovine brains was conducted at the Inter Research Center Uni-versity(PAU), Bandung Institute of Technology. The research was using Completely Randomized Design con-sisting of four treatments and three replications. The treatment were 20 mg kg-1, 35 mg kg-1, 50 mg kg-1 and control. Parameters observed were the distribution of the eggs, egg diameter and fecundity using gravimetric methods. Data were analyzed using analysis of variance. If there are differences among the treatments then continued with Duncan's multiple range test at 5% level. Addition of bovine brain meal in feed with dose of 50 mg kg-1 was give a dominant influence on the size distribution of eggs by 60% from 1.01 to 1.5 mm, egg diameter 0.90 mm, and fecundity of 67 grains g-1. Abstrak Penelitian ini bertujuan untuk menentukan dosis tepung otak sapi pada pakan yang berpengaruh terhadap performa telur dan fekunditas ikan komet. Penelitian dilaksanakan di panti benih Fakultas Perikanan dan Ilmu Kelautan Univer-sitas Padjadjaran pada bulan November 2014 sampai dengan Januari 2015. Pengeringan beku otak sapi dilakukan di Pusat Penelitian AntarUniversitas Institut Teknologi Bandung. Penelitian ini menggunakan metode eksperimental de-ngan Rancangan Acak Lengkap yang terdiri atas 4 perlakuan dan 3 ulangan. Perlakuan yang diberikan yaitu 20 mg kg-1 induk, 35 mg kg-1 induk, 50 mg kg-1 induk dan perlakuan kontrol. Parameter yang diamati yaitu sebaran telur, diameter telur, dan fekunditas relatif menggunakan metode gravimetrik. Data dianalisis menggunakan analisis keragaman dengan uji F untuk mengetahui pengaruh dari setiap perlakuan. Apabila terdapat perbedaan antar perlakuan maka dilanjutkan dengan uji jarak berganda Duncan pada taraf 5%. Penambahan tepung otak sapi pada pakan sebanyak 50 mg kg-1 induk memberikan pengaruh dominan sebaran telur pada ukuran 1,01-1,5 mm sebesar 60%, diameter telur 0,90 mm, dan fe-kunditas relatif sebesar 67 butir g-1.